Epiregulin promotes trophoblast epithelial–mesenchymal transition through poFUT1 and O‐fucosylation by poFUT1 on uPA. (30th December 2019) - Cui, Xinyuan; Wang, Hao; Li, Yaqi; Chen, Tianhong; Liu, Shuai; Yan, Qiu
Abstract: Objectives: The transformation of cytotrophoblasts into mesenchymal‐like extravillous trophoblasts is necessary for successful embryo implantation, and the inadequate transformation may cause abortion. Epiregulin, which is a new growth factor, plays important roles in the reproductive processes. The glycosylation of many proteins in reproduction processes is critical. Protein O‐fucosyltransferase 1 (poFUT1) is the key enzyme for the biosynthesis of O‐fucosylation on the specific glycoproteins. Urokinase‐type plasminogen activator (uPA) contains O‐fucosylated domain on Thr 18 . However, the functions of epiregulin and poFUT1 in the trophoblast epithelial–mesenchymal transition (EMT) process, the regulatory mechanism of epiregulin on poFUT1 and the resulting O‐fucosylated uPA remain unclear. Materials and methods: We employed ELISA and Western blot to detect serum levels of epiregulin and poFUT1 from non‐pregnancy women, pregnancy women and abortion patients. Using two trophoblast cell lines and a mouse pregnancy model, we investigated the underlying mechanisms of epiregulin and poFUT1 in trophoblast EMT process. Results: Serum levels of epiregulin and poFUT1 were higher in pregnant women compared with non‐pregnant women, and their levels were significantly decreased in abortion patients compared with pregnant women. The results showed that epiregulin upregulated poFUT1 expression and increased O‐fucosylation on uPA, which further activated the PI3K/Akt signalling pathway, facilitating EMT behaviour of trophoblast cells and embryo implantation in the mouse pregnant model. Conclusions: Level of epiregulin and poFUT1 is lower in abortion patients than early pregnancy women. Epiregulin promotes trophoblast EMT through O‐fucosylation on uPA catalysed by poFUT1. Epiregulin and poFUT1 may be suggested as the potential diagnostic biomarkers and useful treatment targets for abortion.